The role of Islamic law in protecting the status of women and its impact on building and developing human society - Salameh, Prof. Dr. Muhammad Khalaf Bani Salameh (Sulaimani Journal for Humanities, 2026)
The role of Islamic law was prominent and clear in highlighting the status of women through Quranic verses and Prophetic traditions. These texts demonstrated a clear concern for women due to their active role in building human society. This contrasted sharply with the long periods before Islam when women were deprived of their rightful place and treated as commodities to be bought and sold in previous civilizations and among earlier nations, including the pre-Islamic era and even in contemporary Western civilization. This study addresses the role of Islamic law in protecting women's status and its impact on the development of human society. It examines the role of women throughout human history, their contribution to the family system and societal development, and their status in Islam, particularly their role in building the family. The study arrives at several conclusions, most notably the need to identify the most significant problems facing families and limiting women's participation and role in society. It also explores how Islamic law has worked to protect women's status within the family and society. The study recommends highlighting the role of Islamic law in protecting women's status in public forums through various media outlets.